Diagnosis and treatment of COVID–19 in primary healthcare - Punoševac, Darinka (General Practice, 2022)
COVID-19 pandemic is caused by the SARS-Cov-2 virus and it was first isolated in Wuhan, China, in December 2019. In Primary Healthcare Center (PHC), Krusevac, the outpatient clinic for respiratory infections was formed on March 24th, 2020. Nearly 100.000 medical exams were performed there, up til now. The virus transmission is carried out by airborne droplets, or rarely using contaminated hands. The entrance site of the infection is nose, mouth, or eye mucose. The infection develops in two stages. The first happens in the upper respiratory tract (URT) and lasts 5-7 days, and the second, when the virus descends to the lungs, and from there causes systemic inflammation, primarily of the blood vessels. The diagnosis is based on the personal history, clinical presentation, physical exam, specific viral tests, lab analysis, and eventually, chest X-ray. Therapy is mainly symptomatic, and since March 2021 we got antiviral favipiravir, and in January 2022 another antiviral, molnupiravir, became available. Oral corticosteroids showed promising results in patients with viral pneumonia. Primary healthcare was a dam against the secondary and tertiary healthcare this time, too. As our colleagues worldwide, we were learning in stride, and the process is ongoing. The more people get exposed to the virus, either naturally or by vaccination, the sooner the pandemic will end but not entirely and probably stay with us as a seasonal infection with easier clinical presentation.